2019
DOI: 10.31235/osf.io/ntz52
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Impacts of Environmental, Social, and Governance Factors on Firm Performance: Panel Study of Malaysian Companies

Abstract: Purpose - The ESG factor, which consists of environmental, social, and governance factors, represents the non-financial performance of a company. United Nations Principles for Responsible Investment (UN-PRI) invites investors to consider ESG issues when evaluating the performance of any company. Moreover, nowadays the contribution of corporations towards sustainable development is a major concern of investors, creditors, government, and other environmental agencies. Therefore, the purpose of this paper is to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
48
3
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(65 citation statements)
references
References 0 publications
13
48
3
1
Order By: Relevance
“…Studies exist employing these methods in similar contexts (Lensink, Mersland, Vu and Zamore, 2018;Tebaldi, Nguyen and Zuluaga, 2018;Fufa and Kim, 2018). While many studies have used fixed effects and random effects model for panel data (for example, Glass, Cook and Ingersoll, 2016;Atan et al 2018), Athanasoglou, Brissimis, and Delis (2008) stated that perseverance of bank performance over the time might disturb the following year's return.…”
Section: Generalized Methods Of Moments (Gmm)mentioning
confidence: 99%
See 4 more Smart Citations
“…Studies exist employing these methods in similar contexts (Lensink, Mersland, Vu and Zamore, 2018;Tebaldi, Nguyen and Zuluaga, 2018;Fufa and Kim, 2018). While many studies have used fixed effects and random effects model for panel data (for example, Glass, Cook and Ingersoll, 2016;Atan et al 2018), Athanasoglou, Brissimis, and Delis (2008) stated that perseverance of bank performance over the time might disturb the following year's return.…”
Section: Generalized Methods Of Moments (Gmm)mentioning
confidence: 99%
“…Previous studies found a mixed relationship between CSP and firm financial performance (Orlitzky, Schmidt, & Rynes, 2003). Majority of the studies found a positive relationship between CSP and financial performance (Atan, Alam, Said, & Zamri, 2018;Godfrey et al, 2009;Velte, 2017). However, CSP may influence the financial performance negatively due to stakeholders' negative perception over high emphasise on CSP (Utz, 2018)…”
Section: Social Performance and Financial Performancementioning
confidence: 99%
See 3 more Smart Citations